JIHAD IN ISLAM - Kuntari Madchaini (STAI Al-Washliyah Banda Aceh, 2019)
Understanding the truth of jihad in Islam through its concepts -illustrated in the Koran and Hadith, the books of interpretation, hadith, and fiqh- is the most objective way of getting to know jihad. This is because jihad is a term in Islam that should be judged by its own perspective, and not in the eyes of other reviewers. Therefore, this research aims to uncover the truth of jihad from the Islamic references above to be more proportional in uncovering its nature.